Projecting future disease and economic burdens of heatwave-related preterm birth in China under different climate scenarios - Yayi Li; Xiaoli Sun; Jianxiong Hu; Zhiqing Chen; Qijiong Zhu; Yixiang Huang; Yilin Li; Xinjie Xiao; Xinqi Zhong; Guanhao He; Cunrui Huang; Wenjun Ma; et al. (Environment International)
Background: The increasing frequency of heatwaves poses significant risks for preterm birth (PTB). However, the extent of the disease and economic burdens attributable to heatwave-related PTB in China remains uncertain. Methods: We defined a heatwave event as two or more consecutive days in which the daily maximum temperature exceeded the 90th percentile during 1995–2014, and estimated the burdens of heatwave-related PTB under different Shared Socioeconomic Pathway (SSP) scenarios, including cases, deaths, disability-adjusted life years (DALY), and the value of a statistical life (VSL) from 2015 to 2100, at the city level in China. Results: The number of heatwave-related PTBs showed a fluctuating upward trend from 2015 to 2100 under three SSP scenarios. By the 2090 s, heatwave-related PTB cases per million births are estimated at 2,314.64 (95 %CI: 1,112.30, 3,518.23), 4,335.15 (95 %CI: 2,651.81, 6,020.31) and 5,217.16 (95 %CI: 3,606.26, 6,829.17) under SSP126, SSP370 and SSP585 scenarios, respectively. From the 2020 s to 2090 s, the number of attributable deaths in infants under 1 year is projected to decrease from 19.91 (95 % CI: 11.37, 28.32) to 6.58 (95 % CI: 4.61, 8.51) thousand under SSP585 scenario. Attributable DALY rate is projected to increase after 2023, with DALY mainly in the Sichuan Basin and the Beijing-Tianjin-Hebei Urban Agglomeration. Population-adjusted attributable VSL is projected to increase before the 2040s and then stabilize under SSP126 and SSP370, while showing a sustainedly increasing trend during the 2000s–2090s under SSP585. Conclusions: Heatwaves would impose a significant disease burden from PTB and translate into substantial economic burden, particularly under higher emission scenarios.